2018
DOI: 10.7150/thno.27760
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-inspired conductive nanofibrous membranes repair myocardial infarction by enhancing cardiac function and revascularization

Abstract: The controversy between polypyrrole's (Ppy) biocompatibility and its aggregation on nanofibers impedes application of conductive Ppy-incorporated nanofibers to create engineered cardiac microenvironments. The purpose of this study was to fabricate a functional scaffold for engineering cardiac patches (ECP) using a high concentration of methyl acrylic anhydride-gelatin (GelMA)-Ppy nanoparticles, mussel-inspired crosslinker, and electrospun (ES)-GelMA/polycaprolactone (PCL) nanofibrous membrane.Methods: First, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 65 publications
2
35
0
Order By: Relevance
“…Moreover, the implant of this dual growth factor-loaded patch in a rabbit having undergone AMI evidenced blood vessel sprouting in the patch secured region with consequent improvement of functional regeneration of cardiac tissue [106]. He et al confirmed that neovascularization was accompanied by a reduction in infarct size extension as well as cardiac function improvement in an in vivo study [107].…”
Section: Effect Of Nanoengineered Materials On Vascularizationmentioning
confidence: 93%
“…Moreover, the implant of this dual growth factor-loaded patch in a rabbit having undergone AMI evidenced blood vessel sprouting in the patch secured region with consequent improvement of functional regeneration of cardiac tissue [106]. He et al confirmed that neovascularization was accompanied by a reduction in infarct size extension as well as cardiac function improvement in an in vivo study [107].…”
Section: Effect Of Nanoengineered Materials On Vascularizationmentioning
confidence: 93%
“…Phase separation and salt leaching fabrication methods can process them into porous scaffolds (Figure 2f–g; (Hashizume, Fujimoto, et al, ; Ravichandran et al, ). Electrospinning is a common way to fabricate nano or sub‐micro fibrous scaffolds (Figure 2h; He et al, ), while phase separation can also achieve nano‐fibrous morphology (Figure 2i; Liu et al, ). Additionally, patches with pattern surface were fabricated using film casting (Figure 2j; Cristallini et al, ).…”
Section: Biodegradable Polymeric Cardiac Patchesmentioning
confidence: 99%
“…Copyright 2013, published by Elsevier Ltd. (h) Electrospun GelMA/PCL. Reproduced with permission (He et al, ). Copyright 2018, published by Theranostics.…”
Section: Biodegradable Polymeric Cardiac Patchesmentioning
confidence: 99%
“…[5] Conductive materials such as graphene oxide, PPy, and carbon nanotubes (CNTs) are common raw materials used for conductive scaffolds fabrication. [54][55][56] Third, once therapeutic cells are transplanted into the infarcted region, scaffolds should help retain cells, which require materials to provide plenty of cell adhesion sites. In addition, the degradation rate of the scaffold material needs to match the rate of the production of ECM.…”
Section: Tissue Engineering Strategymentioning
confidence: 99%